Long-term safety and maintenance of efficacy of levodopa-carbidopa intestinal gel: an open-label extension of the double-blind pivotal study in advanced Parkinson's disease patients - Slevin, John T; Fernandez, Hubert H; Zadikoff, Cindy; Hall, Coleen; Eaton, Susan; Dubow, Jordan; Chatamra, Krai; Benesh, Janet (Journal of Parkinson's disease, 2015)
Levodopa-carbidopa intestinal gel (LCIG) is delivered continuously via intrajejunal percutaneous gastrostomy tube. To examine long-term safety, efficacy and quality of life of LCIG in an open-label extension study. Patients received 52 weeks of open-label LCIG treatment following a 12-week double-blind, double-dummy trial in which they were randomized to either LCIG or immediate-release oral levodopa-carbidopa. Patient cohort designation was by receipt of LCIG in the preceding trial randomization (continuing-LCIG vs. LCIG-naïve patients). Sixty-two of 66 subjects in the double-blind proceeded to the open-label extension. Most subjects (95%) reported ≥1 adverse event (AE); only 3 subjects (4.8%) discontinued due to AEs. AE incidence declined gradually over 52 weeks. Serious AEs were reported by 23%. LCIG-naïve patients (N = 29) showed a decrease in "Off" time and an increase in "On" time without troublesome dyskinesia (change from baseline to final visit in mean [SD] hours = -2.34 [2.78] P < 0.001 and 2.19 [3.70] P = 0.005, respectively), while continuing-LCIG patients (N = 33) showed sustained "Off" time duration and further improvement in "On" time without troublesome dyskinesia (-0.42 [2.67] P = 0.377 and 1.00 [2.58] P = 0.036, respectively). The majority of patients in both groups (LCIG-naïve, continuing-LCIG, respectively) were rated 'Much Improved' or 'Very Much Improved' at final visit on the Clinical Global Impression-Improvement scale (69.0%, 69.7%). Continuing-LCIG patients continued to derive benefit from LCIG while the magnitude of improvement among LCIG-naïve patients was similar to that observed for patients on LCIG in the preceding double-blind study. The overall AE profile was consistent with previous phase 3 clinical trials involving the LCIG system.